End-of-Fiber Signals Strongly Influence the First and Second Phases of the M Wave in the Vastus Lateralis: Implications for the Study of Muscle Excitability - Rodriguez-Falces, Javier; Place, Nicolas (Frontiers in Physiology, 2018)
It has been recurrently observed that, for compound muscle action potentials (M wave) recorded over the innervation zone of the vastus lateralis, the descending portion of the first phase generally shows an “inflection” or “shoulder”. We sought to clarify the electrical origin of this shoulder-like feature and examine its implications. M waves evoked by maximal single shocks to the femoral nerve were recorded in monopolar and bipolar configurations from 126 individuals using classical (10-mm recording diameter, 20-mm inter-electrode distance) electrodes and from 8 individuals using small electrodes arranged in a linear array. The changes of the M-wave waveform at different positions along the muscle fibers’ direction were examined. The shoulder was identified more frequently in monopolar (97%) than in bipolar (46%) M waves. The shoulder of M waves recorded at different distances from the innervation zone had the same latency. Furthermore, the shoulder of the M wave recorded over the innervation zone coincided in latency with the positive peak of that recorded beyond the muscle. The positive phase of the M wave detected 20 mm away from the innervation zone was essentially composed of non-propagating components. The shoulder-like feature in monopolar and bipolar M waves results from the termination of action potentials at the superficial aponeurosis of the vastus lateralis. We conclude that, only the amplitude of the first phase, and not the second, of M waves recorded monopolarly and/or bipolarly in close proximity to the innervation zone can be used reliably to monitor possible changes in muscle membrane excitability.